Minimization of Ground Vibration Test Configurations for F-16 Aircraft by Subtractive Modification. (7th November 2019) - Koksal, Sertac; Yildiz, Erdinc Nuri; Yazicioglu, Yigit; Ozgen, Gokhan Osman
Abstract : The certification process of external loads designed for aircraft needs to satisfy various criteria where compatibility with existing systems is one of the essential requirements. Flight flutter testing is a critical part of a certification process that requires many preliminary studies. Computational flutter analysis must precede actual flutter test to determine an approximately safe flight envelope to ensure the safety of the personnel and aircraft. To be able to perform flutter analysis of an aircraft, an accurate structural model such as finite element (FE) model is required. An accurate FE model can be obtained from a coarse model using ground vibration test (GVT) which is also the primary test campaign for certification of a new external load, new aircraft design, or modification on existing aircraft. On the other hand, performing GVT for each configuration of an aircraft is both time consuming and costly. It would be more practical to determine the critical configurations for an aircraft using computational tools and perform actual GVT for those configurations. The objective of this study is to simulate GVT characteristics for downloading and fuel configurations of F-16 aircraft. A novel methodology is proposed where various loading configurations can be simulated by subtractive modification from loaded GVT data so that joint stiffnesses between stores and aircraft need not be identified. The proposed technique decreases the number of necessary physical GVT testing campaigns.